WUCHERERIA BANCROFTI: THE ETIOLOGICAL AGENT OF ELEPHANTIASIS (CIPEEX, 2025)
Parasitology has been of great relevance in the health area, as the study of the parasite-host relationship has helped prevent contact with parasites, aiding treatment and reducing death cases. The objective of this abstract was to describe the main characteristics of lymphatic filariasis. Wuchereria bancrofti is a Nematoda helminth with a heteroxenic biological cycle that parasitizes mammals, transmitted by the insect vector of the genus Culex. This is the species observed in Brazil. These are thin and long worms, with females producing microfilariae.Microfilariae occupy the lymphatic and blood vessels but can also reach the subcutaneous tissue, peritoneal cavity, etc. The intermediate host is the insect Culex quinquefasciatus, while humans act as the definitive host. In the biological cycle, the female is larger than the male. Larvae stages L1 and L2 occur in the mosquito, while the L3 larva is inoculated into the definitive host, where it matures into an adult worm. Mosquitoes become infected during blood meals, transmitting immature larvae.Lymphatic filariasis, popularly known as elephantiasis, is characterized by tissue edema but can go unnoticed with a low parasite load. Acute lymphangitis and lymphadenitis may occur, involving inflammation of lymphatic vessels and nodes, respectively. Symptoms include edema, fever, headache, malaise, local pain, and redness. Since the 1950s, hemoscopic surveys have been conducted nationwide to establish the epidemiology and control of this parasitosis.
Keywords: host-parasite relationship; lymphatic filariasis; edema; muriçoca